Implementation of Islamic Values and Character Education in English Teaching Materials for Students in Islamic Boarding Schools - Dedi Efrizal (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Implementation of Islamic Values and Character Education in English Teaching Materials for Students in Islamic Boarding Schools. Islamic values and character education in English teaching materials for students in Islamic boarding schools are very urgent to be implemented, especially in the world of education because many non-educational student behaviors have penetrated our educational institutions recently, such as the phenomenon of physical violence and verbal abuse, sexual harassment, drug abuse, corruption and abuse that occur at various levels and circles in the school world. After conducting a preliminary study at Modern Darussalam Islamic Boarding School, Kepahiang, it can be concluded that Modern Darussalam Islamic Boarding School, Kepahiang is an educational institution that is very concerned about the importance of Islamic values and character education in the content of various subjects, especially in English subjects. This research use desciptive qualitative approach. In collecting data, the writer used observation, interview, and documentation techniques. This research produced three findings, namely from the aspects of planning, implementation, and evaluation, namely creating an integrative character curriculum, respecting the creativity of students, and strict supervision of morals.Abstrak: Implementasi Nilai-Nilai Islami dan Pendidikan Karakter dalam Bahan Ajar Bahasa Inggris Bagi Santri di Pondok Pesantren. Nilai-nilai islami dan pendidikan karakter dalam bahan ajar bahasa inggris bagi santri di pondok pesantren sangat urgen untuk diimplementasikan, terutama dalam dunia pendidikan karena banyak perilaku santri non-kependidikan yang akhir-akhir ini merambah lembaga pendidikan kita, seperti fenomena kekerasan fisik dan pelecehan verbal, pelecehan seksual, penyalahgunaan narkoba, korupsi dan penyalahgunaan yang terjadi di berbagai tingkatan dan kalangan di dunia sekolah. Setelah melakukan studi pendahuluan di Pesantren Modern Darussalam Kepahiang, dapat disimpulkan bahwa Pesantren Modern Darussalam Kepahiang merupakan lembaga pendidikan yang sangat memperhatikan pentingnya nilai-nilai Islam dan pendidikan karakter dalam muatan berbagai mata pelajaran, khususnya dalam mata pelajaran bahasa Inggris. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Dalam pengumpulan data, penulis menggunakan teknik observasi, wawancara, dan dokumentasi. Penelitian ini menghasilkan tiga temuan yaitu dari aspek perencanaan, pelaksanaan, dan evaluasi yaitu menciptakan kurikulum karakter yang integratif, menghargai kreativitas siswa, dan pengawasan moral yang ketat.